The Impacts of Social Media on National Security: A View from the Northern and South-Eastern Region of Nigeria - Chukwuere, Joshua Ebere; Onyebukwa, Chijioke Francis (International Review of Management and Marketing, 2018)
The social media (SM) platform has reengineered social interaction among peers, businesses, governments and so on. SM platforms are used in advancing social and national insecurity, such as the situation in the northern and south-eastern parts of Nigeria. For some years now, terrorism and propaganda have engulfed the northern part of Nigeria by insurgent groups while separatist groups have also carried out demonstrations in the south-east. Each of these groups is using various kinds of online media to propagate their agenda, and the general public also uses SM platforms to escalate this propaganda, which sometimes is fake news. However, there is no comprehensive study on the role of SM towards the challenges of insecurity confronting the northern and south-eastern regions of Nigeria. This study deployed a quantitative research method through online questionnaires to determine the impacts of Facebook, Twitter and WhatsApp as SM tools on the security challenges confronting the northern and south-eastern parts of Nigeria. The study found that Nigeria’s security climate is very poor, SM is not a threat to Nigeria national security, the participants are uncertain whether Facebook, Twitter and WhatsApp have increased insecurity in the northern and south-eastern parts of Nigeria and many more. Keywords: Social media, new media, Nigerian security, northern and south-eastern, insecurity, security challenges, SM. JEL Classifications: F50; H55; H56; O55 https://doi.org/10.32479/irmm.6852